A Computing Method for Sand Inrush Quantity through a Borehole in Longde Coal Mine - Boyang Zhang; Zhibin Lin (Advances in Civil Engineering)
A quicksand disaster through a borehole occurred in Longde coal mine. A lot of aeolian sand, the volume of which is between 310,000 m3 and 380,000 m3, has submerged into the underground space in about 70.5 h. The volume flux of quicksand cannot be calculated accurately by the empirical method. Based on the method of fluid mechanics, an all-purpose computing method for quicksand disaster through a borehole was proposed. The result shows that the inrush volume of sand into underground space was between 310,000 m3 and 350,000 m3, which was consistent with the actual result. To apply and popularize this method, the impact laws of water yield properties of an aquifer on the volume flux were discussed. The all-purpose computing method can be suitably used for the volume flux calculation of quicksand disaster through the borehole.